A Study of Plate Waste in a Food Service - Yuksel, Aysun; Yılmaz Önal, Hülya (Progress in Nutrition, 2021)
Objective: To determine the amount of plate waste of the personnel eating in a hospital food hall and to evaluate according to the food types. Design: A cross-sectional trial. Setting: Food hall of a state hospital in İstanbul. Main Outcome Measures: Plate wastes by food types. Analysis: In the analysis of quantitative variables, the interactive model was tested with two-way analysis of variance (Two-way ANOVA) for the effects of 2 factors (meal and type of food). Results: During the research, 16,722 people’s plate waste was weighed. 6.2% of the edible food that was served was disposed. The average amount of waste at dinner was found to be less than lunch (p<0.05). According to the type of food, pastry desserts are disposed the least in lunch (1.8%; 95% Cl, 1.67-1.94) and the most in dinner (5.8%; 95% Cl, 4.78-5.50). Conclusions and Implications: In order for countries to create plans for preventing food loss, and waste, they must first conduct waste measurement research in every field of the aspect. Measuring food waste in institutional food services, determining the reasons, and informing the consumers are necessary for the continuation of sustainable development. Consumer awareness of food waste and food insecurity should be evaluated together.